2015
DOI: 10.1155/2015/415458
|View full text |Cite
|
Sign up to set email alerts
|

Trying to Put the Puzzle Together: Age and Performance Level Modulate the Neural Response to Increasing Task Load within Left Rostral Prefrontal Cortex

Abstract: Age-related working memory decline is associated with functional cerebral changes within prefrontal cortex (PFC). Kind and meaning of these changes are heavily discussed since they depend on performance level and task load. Hence, we investigated the effects of age, performance level, and load on spatial working memory retrieval-related brain activation in different subregions of the PFC. 19 younger (Y) and 21 older (O) adults who were further subdivided into high performers (HP) and low performers (LP) perfor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 64 publications
2
18
0
Order By: Relevance
“…Most importantly, the results point toward a more‐efficient or ‘youth‐like’ load‐dependent up‐regulation of the spatial working memory network in older high‐performing subjects . Recent results confirmed these effects, although a different paradigm, a different design, and a different methodological approach were used (e.g., serial vs parallel stimulus presentation; retrieval vs recognition; load levels 4, 5, and 6 vs 1, 3, and 7; different region of interest masks and analysis of variance designs). Nevertheless, particularly for the left dorsolateral prefrontal cortex, activation patterns modulated by performance level and task load are surprisingly similar, which provides further evidence of the validity of these effects (compare left Figure 5A in with bottom Figure 4 in).…”
mentioning
confidence: 75%
“…Most importantly, the results point toward a more‐efficient or ‘youth‐like’ load‐dependent up‐regulation of the spatial working memory network in older high‐performing subjects . Recent results confirmed these effects, although a different paradigm, a different design, and a different methodological approach were used (e.g., serial vs parallel stimulus presentation; retrieval vs recognition; load levels 4, 5, and 6 vs 1, 3, and 7; different region of interest masks and analysis of variance designs). Nevertheless, particularly for the left dorsolateral prefrontal cortex, activation patterns modulated by performance level and task load are surprisingly similar, which provides further evidence of the validity of these effects (compare left Figure 5A in with bottom Figure 4 in).…”
mentioning
confidence: 75%
“…Previous studies have implicated the ventrolateral PFC (VLPFC; including the IFG) in the selection, comparison, and judgment of task-relevant information (Glahn et al, 2002;Owen, McMillan, Laird, & Bullmore, 2005), and this region is further believed to support storage processes during WM performance (Bauer et al, 2015;Glahn et al, 2002;Owen, 2000;Owen et al, 1999;Wager & Smith, 2003). Previous studies have implicated the ventrolateral PFC (VLPFC; including the IFG) in the selection, comparison, and judgment of task-relevant information (Glahn et al, 2002;Owen, McMillan, Laird, & Bullmore, 2005), and this region is further believed to support storage processes during WM performance (Bauer et al, 2015;Glahn et al, 2002;Owen, 2000;Owen et al, 1999;Wager & Smith, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, using a delayed-recall spatial navigation task, Crespo-Garcia et al (2016) found that decreased theta activity within hippocampal, insular, and occipitotemporal regions during encoding was related to greater accuracy during recall. Concerning SWM load effects, there is some evidence that individuals who perform better on SWM tasks recruit left prefrontal regions more strongly as SWM load increases, relative to individuals who perform worse on such tasks (Bauer et al, 2015;Nagel et al, 2009). However, only one study has attempted to identify the oscillatory responses underlying such load-related behavioral differences.…”
Section: Introductionmentioning
confidence: 99%
“…Another option to examine the impact of behavioral performance on brain activation is the comparison between high- and low-performing individuals in different age cohorts. An fMRI study of Bauer and colleagues, for example, revealed that older high-performers similar as younger high-performers showed increasing prefrontal activation with increasing working memory load [86]. This ‘youth-like’ pattern was less differentiated in older individuals but pointed toward an efficient recruitment of neural resources at increasing task demands.…”
Section: Neurocognitive Changes Associated With Normal Agingmentioning
confidence: 99%
“…Hypothetical model of left dorsolateral prefrontal cortex (DLPFC) activation modulated by age and performance level (particularly based upon the results of Nagel et al [69] and Bauer et al [86]). The bar chart indicates a flexible upregulation of DLPFC activation in YHP as neural response to increasing load.…”
Section: Fig1mentioning
confidence: 99%